Analisis Pengaruh Penerapan Model Pembelajaran Sains Teknologi Masyarakat Terhadap Hasil Belajar Siswa - Suarni, Gita Lilis; Rizka, M A; Zinnurain, Zinnurain (Jurnal Paedagogy, 2021)
This study aimed to analyze the influence of the model of learning science society technology to the learning outcomes of students at SMP Negeri 3 Batukliang. This research uses experimental methods. The sample in this study were 24 students of class VIIIC. This research data collection using tests, observation, and documentation. While the data analysis technique of this study used the t-test. These results indicate that the value t count bigger than t-table at significance level of 5% with db = 24-1 = 23 (7.768> 2,069), so this research can be concluded that there is influence of science learning model community technology on learning outcomes students in biology class VIII at SMP Negeri 3 Batukliang.